Clinical characterisation of the CABP4-related retinal phenotype. Issue 3 (25th October 2012) - Khan, Arif O; Alrashed, May; Alkuraya, Fowzan S
Abstract : Background: Calcium binding protein 4 (CABP4), specifically located in photoreceptor synaptic terminals, has been associated with congenital stationary night blindness based on this clinical diagnosis being made for three individuals from two Swiss families with CABP4 mutations; however, the few reported cases limit phenotype–genotype correlation. We expand the number of reported patients with CABP4 mutations and clinically characterise the CABP4 -related phenotype. Methods: A retrospective case series of 11 individuals (age 2â 26 years; four consanguineous families) with early-onset retinal dysfunction found to harbour CABP4 mutations after a strategy of homozygosity analysis and/or candidate gene testing. Results: The 11 patients from four families harboured the same homozygous CABP4 mutation (c.81_82insA; p.Pro28Thrfs*4) and shared a common haplotype. All patients had congenital nystagmus, stable low vision, photophobia and a normal or near-normal fundus appearance. None complained of night blindness when specifically questioned. Eight had hyperopic cycloplegic refractions (≥+ 1.00 dioptre). Electroretinography showed an electronegative waveform response to scotopic bright flash, near-normal to subnormal rod function, and delayed and/or decreased cone responses or was non-recordable. Although these and previously reported families with homozygous mutations were labelled with different clinical diagnoses, all had similar clinical features. Conclusion: These typical clinical features, which do not include a symptom of night blindness, suggest CABP4 mutations. The phenotype is best uniformly termed congenital cone-rod synaptic disorder. In Saudi Arabia a founder homozygous c.81_82insA CABP4 mutation is a recurrent cause.